Acoustic Spatiality - Brandon LaBelle ([sic])
Experiences of listening can be appreciated as intensely relational, bringing us into contact with surrounding events, bodies and things. Given that sound propagates and expands outwardly, as a set of oscillations from a particular source, listening carries with it a sensual intensity, whereby auditory phenomena deliver intrusive and disruptive as well as soothing and assuring experiences. The physicality characteristic of sound suggests a deeply impressionistic, locational "knowledge structure" – that is, the ways in which listening affords processes of exchange, of being in the world, and from which we extend ourselves. Sound, as physical energy reflecting and absorbing into the materiality around us, and even one's self, provides a rich platform for understanding place and emplacement. Sound is always already a trace of location.Such features of auditory experience give suggestion for what I may call an acoustical paradigm – how sound sets in motion not only the material world but also the flows of the imagination, lending to forces of signification and social structure, and figuring us in relation to each other. The relationality of sound brings us into a steady web of interferences, each of which announces the promise or problematic of being somewhere.